First-Principle Investigation into Mechanical Properties of Al6Mg1Zr1 under Uniaxial Tension Strain on the Basis of Density Functional Theory - Lihua Zhang; Jijun Li; Jing Zhang; Yanjie Liu; Lin Lin (Metals, 2023)
The influences of uniaxial tension strain in the x direction (εx) on the mechanical stability, stress–strain relations, elastic properties, hardness, ductility, and elastic anisotropy of Al6Mg1Zr1 compound were studied by performing first-principle calculations on the basis of density functional theory. It was found that Al6Mg1Zr1 compound is mechanically stable in the range of strain εx from 0 to 6%. As the strain εx increased from 0 to 6%, the stress in the x direction (σx) first grew linearly and then followed a nonlinear trend, while the stresses in the y and z directions (σy and σz) showed a linearly, increasing trend all the way. The bulk modulus B, shear modulus G, and Young’s modulus E all dropped as the strain εx increased from 0 to 6%. The Poisson ratio μ of Al6Mg1Zr1 compound was nearly unchanged when the strain εx was less than 3%, but then it grew quickly. Vickers hardness HV of Al6Mg1Zr1 compound dropped gradually as the strain εx increased from 0 to 6%. The Al6Mg1Zr1 compound was brittle when the εx was less than 4%, but it presented ductility when the strain εx was more than 4%. As the strain εx increased from 0 to 6%, the compression anisotropy percentage (AB) grew and its slope became larger when the strain εx was more than 4%, while both the shear anisotropy percentage (AG) and the universal anisotropy index (AU) first dropped slowly and then grew quickly. These results demonstrate that imposing appropriate uniaxial tension strain can affect and regulate the mechanical properties of Al6Mg1Zr1 compound.